Dystopian Book Report - Simoni, Zachary (TRAILS: Teaching Resources and Innovations Library for Sociology, 2017)
This assignment requires students apply sociological concepts to a dystopian novel. Dystopian literature is chosen because they are littered with examples of sociological concepts and develop sociological imagination while remaining entertaining and engaging. Students begin by choosing a dystopian novel from a list provided by the instructor. Each dystopian novel is related to several sociologically relevant issues. For instance, A Handmaids Tale allows students to apply sociological concepts such as patriarchy, gender roles and sexual abuse, whereas 1984 allows students to discuss the relevance of discourse as a form of control, totalitarianism and symbolic power. Additionally, theoretical perspectives can be applied as well, including Durkheim, Marx, Weber or Goffman to name a few. In a short introduction, students briefly summarize the plot and characters of the novel. Next, students strengthen their understanding of sociological concepts by applying relevant sociological concepts discussed in their dystopian novel. Lastly, students develop sociological imagination by connecting themes and motifs from the dystopian novel to the norms and values of contemporary American society.